Development of Online Learning Quiz and Educational Game Using Word Walls in Mathematics for Grade 10 - Kharisma Indah Lestari; I Nyoman Arcana; Agustinus Eko Susetyo; Krida Singgih Kuncoro (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
This research aims to produce and determine the feasibility of quiz and educational game using Word Wall that are suitable for online learning of quadratic inequality, rational, and irrational for grade X. This research method is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research result is learning media in quiz and educational game using Word Wall for quadratic inequality, rational, and irrational material. The feasibility test of materials and media on quiz and educational game resulted in a percentage of 77% and 79,1% with a decent category. The attractiveness of quiz and educational game resulted in a percentage of 81% in the limited trial and 82,2% in the field trial, both of which were in the very interesting category. The results of the correlation test obtained a positive and significant correlation between student responses and student learning outcomes. The implication is that this development product can be used as a student learning tool, and it is recommended that teachers can develop Quiz and educational game using Word Wall on other materials.